Genetic risk factors in cardiovascular disease in the South African population - Scholtz, C. L.(Charlotte Latitia) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Med. Sc.) -- University of Stellenbosch, 1998.